2021
DOI: 10.1111/iwj.13570
|View full text |Cite
|
Sign up to set email alerts
|

Successful improved peripheral tissue perfusion was seen in patients with atherosclerosis after 12 months of treatment with aged garlic extract

Abstract: Patients with arteriolosclerosis have impaired microvascular perfusion leading to impaired wound healing. Aged garlic extract has shown to have a positive impact on vascular elasticity. The present study aimed to assess the effect of long‐term treatment with AGE on peripheral tissue perfusion in patients with confirmed atherosclerosis. Ninety three patients with a CT‐scan confirmed coronary artery arteriolosclerosis were randomised in a double‐blind manner to placebo or 2400 mg AGE daily for 1 year. Peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Recently, the CORDIOPREV study [ 35 ], a randomized, double-blind, controlled trial, showed that long-term dietary intervention with either the Mediterranean diet or a low-fat diet significantly improved skin microvascular endothelial function in over 1000 coronary patients. Regarding garlic-derived products, Lindstedt et al [ 38 ] reported a significant increase of 21.6% in the relative change of PORH in patients with atherosclerosis consuming aged garlic extract for 12 months. This result is in line with our findings, as we observed an increase of 18.8% in PORH in the purple garlic oil group, even after a shorter intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the CORDIOPREV study [ 35 ], a randomized, double-blind, controlled trial, showed that long-term dietary intervention with either the Mediterranean diet or a low-fat diet significantly improved skin microvascular endothelial function in over 1000 coronary patients. Regarding garlic-derived products, Lindstedt et al [ 38 ] reported a significant increase of 21.6% in the relative change of PORH in patients with atherosclerosis consuming aged garlic extract for 12 months. This result is in line with our findings, as we observed an increase of 18.8% in PORH in the purple garlic oil group, even after a shorter intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…The lower values of skin temperature and tissue oxygen saturation at two timepoints in the healthy participant group might be explained as increasing age is an independent risk factor for the development of atherosclerosis [ 35 ] and due to that impairs microcirculation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modern pharmacological studies have shown that aged garlic extract (AGE) reduces the risk of heart disease and dementia because of its multiple pharmacological effects including antioxidative stress, anti-inflammation, and lipid metabolism regulation ( 111 ). A clinical study of 93 arteriosclerosis patients aged 40–75 years found that AGE may effectively increase peripheral tissue perfusion and microcirculation by increasing NO release and improving endothelial function after 12 months of treatment ( 112 ). Moreover, after administration to mice, AGE increased NO production by 30%–40% via activation of constitutive NO synthase (cNOS), which was conducive to further vasodilation ( 113 ).…”
Section: Potential Drugs For the Prevention And Treatment Of Cardioge...mentioning
confidence: 99%